Non-lethal suicidal behavior in university students of Spain during COVID-19 - Ramos-Martín, Javier; Pérez-Berlanga, José Manuel; Oliver, Jesús; Moreno-Küstner, Berta (Frontiers in Psychiatry, 2023)
Background: Suicide is the fourth external cause of death in the world, in persons between the ages of l5 and 29. The objectives of this study were to measure the prevalence of suicidal behaviour in university students and analyse the relationship of suicide risk with psychological distress, resilience, and family and social support. Methods: An observational and transversal study wherein the students at the University of Malaga (Spain) completed an online questionnaire which included items from different scales, sociodemographic and academic questions, and the subjective impact of the COVID-19 pandemic. Descriptive analyses and prevalence rates of suicidal behavior were calculated, and bivariate analyses, multiple linear regression, and a mediation and moderation analyses were conducted. Results: A total of 2,212 students completed the questionnaire. The prevalence of the last 6 months was 30.4% wishing for death, 14.7% suicidal ideation, 5% self-harm injuries, and 0.5% suicide attempts. Psychological distress, family and social support were linked to the risk of suicide. Lastly, resilience and family support measure and moderate the relation between psychological stress and suicide risk. Conclusions: Psychological distress is a risk factor for suicidal behaviour, while resilience and family and social support are linked to a lower risk of suicide.